Avoiding Common Conflicts of Interest in the Lawyer-Client Relationship - Hunter, Richard J.; Shannon, John H. (Advances in Social Sciences Research Journal, 2022)
There are several areas in the law where conflicts of interest commonly occur in the context of the lawyer-client relationship. This article, which is Part II of a three-part series on issues relating to the lawyer-client relationship, will explain two of the main conflicts that may occur: simultaneous representation of clients with differing or conflicting interests and personal conflicts of interest between a lawyer and a client. In addition, the paper will discuss the special considerations inherent in contingent fee arrangements.